IMPLEMENTASI ALGORITMA ADAPTIVE WATERMARKING PADA PELABELAN IDENTITAS FILE CITRA DIGITAL - Darwis Robinson Manalu (Universitas Methodist Indonesia, 2015)
Watermarking is now well known and popular as one of the solutions to protect files and digital media by entering information such as digital signs into the core of the multimedia objects with an invisible state and reliably in conditions that exploit the contents of the digital media. The information included in the image can be text, logos or audio. Labelling is done with adaptive watermarking techniques to calculate phases of the pixel values of the logo file (watermark), calculate the DCT coefficients (Discrete Cosine Transform) digital images, digital image modifying DCT coefficients according to bit files logo, reconstruct a digital image by performing inverse DCT, extracting files logo of the image that has been watermarked. The extracted watermark data is then compared with the original watermark data by calculating the Bit Error Rate (BER), which is the ratio between the number of bits that one of the bits as a whole. From the results of the testing that has been done on the application that is designed may inserting a message in the form of the image into a digital image file, inserting a message in the form of text into image files, the extraction process penyisip of file watermarking and can do the comparison value BER (Bit Error Rate).